Decreased mucosal adhesion of Lactobacillus species in patients with inflammatory bowel disease - Saeideh Najafi; Fattah Sotoodehnejadnematalahi; Mohammad Mehdi Amiri; Mohammad Reza Pourshafie; Mahdi Rohani (Babol University of Medical Sciences, 2022)
Background: Probiotic Lactobacillus spp. modulate immune response via interactions of their binding proteins with epithelial cells. We studied the presence of attachment protein-encoding genes (mub1, mub2, and mapA) in Lactobacillus strains with probiotic features isolated from inflammatory bowel disease (IBD) patients and their attachment strength relative to healthy individuals. Methods: Bacterial strains have been isolated from stool samples of 35 healthy and 23 IBD volunteers. Lactobacillus spp. were identified using PCR. Strains with probiotic features were determined by testing resistance against acid and bile. Isolates were assigned as non-adhesive, adhesive, and strongly adhesive strains based on the number of attached bacteria to epithelial cells. Finally, PCR was used to detect the presence of mub1, mub2, and mapA genes. Results: Probiotic lactobacilli were isolated from 35/35 and 9/23 of healthy and IBD individuals and yielded a total of 87 and 28 strains, respectively. The Mub1 gene was detected in 95.4% and 100% (p>0.05), mub2 in 95.4% and 89.3% (p>0.05), and mapA in 94.3% and 78.6% (p<0.05) of healthy and IBD isolates, respectively. The numbers of bacteria attached to epithelial cells in healthy and IBD isolates were respectively 33.68±6.00 and 12.23±3.87 in non-adhesive, 71.3±10.83 and 42.17±1.33 in adhesive, 124.40±8.59 and 104.67±5.50 in the strongly adhesive group (p< 0.05). Conclusion: Less Lactobacillus spp. with weaker attachments to epithelial cells colonize the gut in IBD than healthy individuals. These findings suggest the beneficial role of probiotics in the management of IBD.